1992
DOI: 10.1029/91ja03156
|View full text |Cite
|
Sign up to set email alerts
|

Substorm intensifications and field line resonances in the nightside magnetosphere

Abstract: Magnetometer and HF radar data often indicate the presence of magnetohydrodynamic, field line resonances in the nightside magnetosphere. These resonances have frequencies of about 1.3, 1.9, 2.6, and 3.4 mHz and are due to cavity modes or waveguide modes which form between the magnetopause and turning points on dipolelike magnetic shells. Energy from these cavity modes tunnels to the field line resonances which are seen in the F region by the HF radar and on the ground by the magnetometers. The presence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(181 citation statements)
references
References 59 publications
9
171
1
Order By: Relevance
“…8a) and thus would map to a location in the near-Earth magnetotail as suggested by e.g. Samson et al (1992), Samson (1994), andYeoman et al (1994). The poleward expanding auroral structure moves initially at 0.9 km s )1 poleward, slowing to 0.6 km s )1 by 71.5°latitude.…”
Section: Discussionmentioning
confidence: 96%
“…8a) and thus would map to a location in the near-Earth magnetotail as suggested by e.g. Samson et al (1992), Samson (1994), andYeoman et al (1994). The poleward expanding auroral structure moves initially at 0.9 km s )1 poleward, slowing to 0.6 km s )1 by 71.5°latitude.…”
Section: Discussionmentioning
confidence: 96%
“…As shown by J. Samson and his group, both from observational and theoretical grounds (see Samson et al, 1992;Samson and Rankin, 1994;Rankin et al, 1994;Liu et al, 1995), non-linear standing lowfrequency waves in the mHz range can be intimately related to the arcs' formation and their multiplicity. In this theory the resonances are fed by broad-band noise in the system, and it was shown that auroral electrons accelerated by FA electric field due to large k ⊥ in the Alfven wave can reach typical auroral energies in a steady state.…”
Section: Non-linear Standing Alfven Waves In the Mhz Range And Multipmentioning
confidence: 99%
“…By themselves monochromatic oscillations at the very-low-frequency range (about 1 ± 5 mHz) connected with ®eld line resonances (FLRs) on the auroral magnetic ®eld lines, are frequently measured by ground based magnetometers and HF radars (e.g., Samson et al, 1992). They may be produced by surface waves excited by plasma pressure pulses in solar wind on the dayside magnetosphere and traveling along inner plasmasheet boundary layers, or by some magnetospheric cavity modes.…”
Section: Eigenfrequencies Of Flrs and Numerical Simulationsmentioning
confidence: 99%
“…Because FLRs and associated auroral arcs are very narrow in latitude and practically homogeneous in local time (Greenwald and Walker, 1980;Samson et al, 1992), the azimuthal variation of the solutions can be ignored (d y 0) in the lowest approximation. The twodimensionality of the problem then eliminates the strong vector (E Â B) nonlinearity in the model, and only weak nonlinear terms associated with the density disturbance survive.…”
Section: Reduced Two-¯uid Modelmentioning
confidence: 99%